Felietonistyka sportowa - w kręgu faktów i mitów - Iwańczyk, Patryk (Stylistyka, 2019)
The purpose of this article is to file up some kind of gap in research in the field of media, studies by characterising writing of two columnists publishing after year 1989 in a sports weekly “Piłka Nożna” - Janusz Atlas and Waldemar Lodziński. Atlas,columns were published as apart of Sytuacje podbramkowe cycle, Lodzinski’s ones - Rzut z autu. Analyses designed for this publication fit the acknowledged and frequently used concept of linguistic genetics. In view of research material’s character (publicistic texts), achievements of researchers representing the movement of philological media studies turned out to be very important. The article contains analysis of gathered press material in terms of its genre belongingness and characteristic linguistic treatments. Moreover, the article is anattempt to break the stereotype of sports journalist which shows tchem as someone specialised in only one, very narrow field (specific and disdained by most people) and unable to use Polish capably. Completely different conclusions come from columns’ analysis-both publicists seem to be intelligent, lettered erudites gifted with writing talent. What is more, columnists successfully don various communication masks in their texts of a taunter, acritic, anadviser or ateacher-to diversify their contact with readers.